ISSUES REGARDING THE FLOOD IMPACT ON THE HERPETOFAUNA HABITATS FROM RIPARIAN AREAS FROM BARCĂU BASIN - V. NEMES; C. SERAC; A. CAPONY; W. KLOK (Aerul şi Apa: Componente ale Mediului, 2011)
Issues regarding the flood impact on the herpetofauna habitats from riparian areas. Flood risk management measures have a major effect on biodiversity conservation of wetlands and riparians areas. Therefore, understanding the need for cooperation and collaboration of all stakeholders (governmental and non-government) in planning and flood risk management in line with European requirements, respectively Habitat directive in association with the domestic law.This paper aims to highlight the importance of riparian areas developed at the interface between terrestrial and aquatic systems, who besides his role in the delineation of ecosystems and the complex functions they perform: loading / discharging groundwater, flood control,protection against erosion, retention of nutrients and export of biomass, protection, microclimate stabilization has a major role in the conservation of specific habitats of these environments, being the least affected by anthropogenic activity,so that relations found between the "living world" and natural support are the most solid.Because the decline of amphibians has direct and visible effects on ecosystem structure, there is an acute need for optimization of the local reproductive populations of amphibians is required for appropriate management of habitats such as breeding and feeding habitats. Only protection of aquatic habitats (breeding) has little value if terrestrial habitats used for feeding amphibians are destroyed.